2020
DOI: 10.3390/ijerph17061826
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Occurrence of fimA Genotypes of Porphyromonas gingivalis in Periodontal Health and Disease

Abstract: Porphyromonas gingivalis is regarded as a “keystone pathogen” in periodontitis. The fimbria assists in the initial attachment, biofilm organization, and bacterial adhesion leading to the invasion and colonization of host epithelial cells. The present study aimed to investigate the occurrence of fimA genotypes in patients with chronic periodontitis and healthy individuals in the Indian population, and to study their association with the number of P. gingivalis cells obtained in subgingival plaque samples of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…We found that most of the tested clinical strains were weak activators of TLR2. Importantly, most carried type II and IV FimA in line with clinical data showing that these types of FimA are the most prevalent fimbriae genotypes detected in periodontitis patients (57)(58)(59). Gene swap studies show that expression of type II (60,61) and IV (62) fimbriae correlates with increased adhesion and invasiveness of P. gingivalis, while type I fimbriae-bearing isolates are more virulent (60).…”
Section: Discussionsupporting
confidence: 75%
“…We found that most of the tested clinical strains were weak activators of TLR2. Importantly, most carried type II and IV FimA in line with clinical data showing that these types of FimA are the most prevalent fimbriae genotypes detected in periodontitis patients (57)(58)(59). Gene swap studies show that expression of type II (60,61) and IV (62) fimbriae correlates with increased adhesion and invasiveness of P. gingivalis, while type I fimbriae-bearing isolates are more virulent (60).…”
Section: Discussionsupporting
confidence: 75%
“…Once this is done, major new phenotypes emerge, and disease processes begin. Ongoing Pg genotyping work (Immoratii et al, unpublished studies) and others [141] have demonstrated and suggest that specific sets of virulence genes of Pg exist (fim A). Assuming that when this transformation occurs or the direct infection with virulent genotypes of Pg occurs, the entirety of the processes described in this paper ensue.…”
Section: The Primary Oral-neurogenic Pg Omv Modelmentioning
confidence: 94%
“…These advantages include sensitivity, simplicity, specificity and rapidity. 18,19 Moreover, it is specific for identification of P.g . The 16S rDNA PCR method was used in this investigation to detect P.g, and the findings showed that it was specific and sensitive for P.g detection.…”
Section: Discussionmentioning
confidence: 99%